PENYELESAIAN SENGKETA KEPEGAWAIAN AKIBAT PENJATUHAN HUKUMAN DISIPLIN - Ade Kosasih (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2017)
Abstract: An understanding of the rights and efforts that civil servants can take in facing employment disputes arising from the imposition of disciplinary punishment of civil servants, needs to be improved in order to avoid the act of arbitrariness (or willekeur) or action beyond the authority (ultra vires) conducted by the organ of state administrative office. The mechanisms and stages of dispute resolution in the field of personnel, has a variety of channels based on disciplinary violations committed, types of sentences handed down, and the level of position of officials who are authorized to punish. These channels, some through the Administrative Objections and Administrative Appeals. If only through Administrative Objection, then the next stage is the filing of a lawsuit to the State Administrative Court, whereas if the stages are through Administrative Appeals, the first level lawsuit shall be submitted to the Administrative High Court as a first instance court.